Using PAT for Energy Recovery and Pressure Reduction in Water Distribution Networks - Hamed Mohammadi; Mahnaz Ghaeini-Hessaroeyeh; Ehsan Fadaei-Kermani (Journal of Hydraulic Structures)
Leakage is one of the main problems of urban water distribution networks. Leakage control and management can play an important role in increasing network efficiency and reducing water loss. Pressure reduction in water distribution networks is usually done using Pressure reducing valve (PRV), while the energy dissipated from head loss can be recovered to generate hydropower. In this study, the possibility of using pump as turbines (PATs) instead of PRVs in a water distribution network has been investigated. Regarding this purpose, the genetic algorithm is used by MATLAB software, in which the hydraulic model of the water distribution network is carried out in WaterGEMS software. At first, the aim of optimization is to determine the optimum output of PRVs. Then after replacing the PRVs with the PATs, the optimal curve for the PATs can be determined. Results show that the use of PATs to control the pressure is effective, so that compared to the basic model, the leakage rate has decreased by about 33% and the Nodal Pressure Reliability Index (NPRI) has increased by 0.41. Moreover, the nodal pressures have been significantly reduced, and the average pressure of the network decreased by 58%.